Writing freedom : South Asian voices - edited by Radha Chakravarty; Chakravarty, Radha; Hossain, Selina 1947- (Dhaka : University Press Limited, 2010)
Collection of poetry, prose, fiction, drama, satire, and autobiography from South Asia, highlighting differenct facets of the idea of freedom, written in English and translated into English from various South Asian languages.
Shamim
Keywords: South Asian literature -- 20th century -- Translations into English; South Asian literature -- 21st century -- Translations into English; South Asian literature (English) -- 20th century; South Asian literature (English) -- 21st century; Liberty in literature